Les notions de fourniture de services et de libre circulation des personnes dans l’Accord de libre-échange canado-américain - Legendre, Michel (Assurances)

(untitled) (HEC Montréal, 1990)
We wish to thank Me Michel Legendre for allowing us to publish a text presented at a conference on free trade held last December 7 for the clients of the firm Desjardins Ducharme. The author discusses two main themes: the first deals with providing the services outlined in Chapter 14 of the Agreement: agriculture, mining and forestry development, construction, commercial distribution insurance and real estate. This chapter also applies to related sectors such as architecture, tourism, computer services and telecommunications. The second theme covers the unrestricted travel and temporary stay of individuals in the respective territories discussed in Chapter 15 of the Agreement. The author briefly describes the various mechanisms contained in the Agreement with respect to these services.